0187 The Effects of Nocturnal Aircraft Noise on Self-Reported Sleep. (27th May 2020) - Casario, K; Howard, K; Smith, M G; Rocha, S; White, M; Basner, M
Abstract: Introduction: Nocturnal traffic noise can fragment sleep through cortical arousals and induce self-reported sleep disturbance. Here we present data gathered around Atlanta International Airport in a pilot field study on the effects of aircraft noise on sleep. Methods: N=34 subjects participated in a five night in-home study. Every night, subjects recorded noise inside their bedroom, and completed questionnaires the following morning containing items on sleep latency; number of awakenings; sleepiness (Stanford Sleepiness Scale); 11-point scales on sleep quality, tiredness, ease of falling asleep and calmness or restlessness of sleep; and a 5-point scale on sleep disturbance by noise. We analyzed the effect of both the average ( L AEq, sleep ) and maximum ( L AS, max, sleep ) aircraft noise level during a subject's sleep period for each questionnaire outcome in repeated measures multiple regression adjusted for the number of aircraft noise events during sleep, sex, age, and if the window was open or closed. Results: A total of 165 sleep questionnaires (97.1% of expected) were completed. Self-reported awakenings increased by n=0.051 per decibel (dB) L AS, max, sleep (p<0.001). An increase in L AS, max, sleep was associated with a significant increase in tiredness (0.118/dB, p=0.005). There was a significant effect of sex on tiredness in the L AEq, sleep model, whereby men were less tired than women. There were no significant effects of L AEq, sleep on any questionnaire outcomes. Conclusion: There was some evidence for adverse effects of aircraft noise on self-reported sleep outcomes. Effects were predominantly found for maximum rather than average noise exposure during the sleep period, stressing the importance of individual noise events for sleep. A larger-scale, adequately powered National Sleep Study will be conducted to better understand the observed effects. Support: This research was funded by the U.S. Federal Aviation Administration Office of Environment and Energy through ASCENT, the FAA Center of Excellence for Alternative Jet Fuels and the Environment, project 017 through FAA Award Number 13-C-AJE-UPENN-011 under the supervision of Natalia Sizov. Any opinions, findings, conclusions or recommendations expressed in this material are those of the authors and do not necessarily reflect the views of the FAA.